New Format Idea in Dissolution Application Political Parties in Indonesia - Efendi Ibnususilo; Faishal Taufiqurrahman; Tomy Supriadi (Universitas Muhammadiyah Sumatera Utara, 2022)
This research formulates several problems, namely: 1) why do reasons and applicants for the dissolution of political party in Indonesia need to be extended in the request?, 2) how is the ius constituendum of the stage of the application for the dissolution of political party in Indonesia? The research method used a juridical normative method by using a philosophical approach and a legislative approach. The results of the research show that corruption must also be included in one of the reasons for the dissolution of a political party, because corruption is a crime that can cause harm for the community. As for the extension of applicants, the urgency can be viewed from four factors. First, the principle of popular sovereignty that adopted by Indonesia. Second, the concept of rechtsstaat that adopted by Indonesia. Third, giving the government the role to be the only applicant in the application for dissolution of a political party will obstruct the process of supervision of political party carried out by the people. Fourth, one of the political party financial resources are from the APBN / APBD, so people reserve the right for the accountability of the use of APBD/APBN by political party. There are two stages in the constituendum of the dissolution of political parties in Indonesia, namely: 1) the stage of submitting an application to the Constitutional Court, 2) the stage of trial in the Constitutional Court. The trial stage consists of five stages: First, preliminary examination. Second, the follow-up trial. Third, the verification process. Fourth, Judicial Consultation Meeting (JCM). Fifth, the reading of the decision by the constitutional judges